Keep it in the family - right to propety and family-owned businesses sucession - Xavier, Rita Lobo (2020)
In Portugal Family Business Represent 70% - 80% Of All The Enterprises, They Are Responsible For 50% Of Employment And For 2/3 The GDP (Gross Domestic Product). Portuguese Constitution Recognizes Right To Property As A Fundamental Right And The Freedom To Dispose Of The Property Upon Death But There Are Many Legal Restrictions To Mortis Causa Transmission As Portuguese Legal System Grants A Part Of The Inheritance Assets To Some Members Of The Family Of The Deceased. Sooner Or Later, Family Enterprises Face The Problem Of Transition To The Next Generation And Researchers Have Pointed Out That The Lack Of Succession Planning May Lead To The Closure Of Family Business. The Disputes Among Heirs Disturb The Enterprise As Portuguese Law Has Not Yet Adopted A Solution Protecting The Continuance Of The Business In The Family When Several Heirs Claim Their Share Of The Enterprise And Require To Be Paid On Cash. Problems May Arise Even When One Heir Wants To Go On In The Business And Need To Pay The Others That Don´T Want To Stay In The Business. It Is Urgent To Create Rules To Facilitate The Family Businesses’ Succession Which Is A Moment Very Difficult To This Kind Of Business. This Paper Enlightens The Specific Needs To Protect The Family Businesses And The Right Of Property Concerning Means Of Production, Aiming To Find Out Whether Under The Portuguese Constitution May The Family Businesses Have A Special Regime.